Wear-resistant heat-conducting silica gel fabric and preparation method thereof
Through the modification of porous sheet boron nitride and chemical bond grafting technology, combined with vinyl silicone oil and hydrogen-containing silicone oil, the problem of insufficient thermal conductivity and friction performance of thermal silicone tape is solved, and high thermal conductivity, low thermal resistance and low friction are achieved The coefficient of wear-resistant thermally conductive silicone tape has expanded its application areas.
Patent Information
- Application Number
- CN202411460645.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
The existing thermal silicone tape has shortcomings in thermal conductivity and friction performance, resulting in increased thermal resistance and poor friction performance, limiting its application potential in high-precision and high-demand fields.
Porous sheet boron nitride is used as the basic material, and is modified by hydroxylation and chemical bond grafting of saturated fatty acids to form a thermal filler, and is mixed with vinyl silicone oil and hydrogen-containing silicone oil in a certain proportion and coated on the surface of glass fiber cloth. The curing and forming is formed by chemical addition reaction to form abrasion-resistant thermally conductive silicone tape.
It significantly improves the thermal conductivity and friction resistance of thermal silicone tape, reduces the friction coefficient and broadens its application prospects.
Smart Images

Figure CN119287673A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of abrasion-resistant thermally conductive silicone cloth, and in particular to abrasion-resistant thermally conductive silicone cloth and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, especially the high integration and miniaturization of electronic equipment, the demand for thermal conductive materials is becoming increasingly urgent. As a key medium for heat transfer, thermal conductive materials play an irreplaceable role in ensuring the stable operation of electronic equipment and extending its service life. Thermal conductive silicone cloth, as an advanced material that combines high thermal conductivity, good flexibility and easy processing, has become the preferred material in many fields, especially in electronic equipment heat dissipation solutions.
[0003] The core components of thermally conductive silicone cloth currently on the market mainly include thermally conductive fillers and silicone rubber matrix. Although thermally conductive fillers, such as alumina and aluminum nitride, can effectively improve the thermal conductivity of the material, the physical mixing method in the traditional preparation method often increases the local thermal resistance due to uneven dispersion of the filler, and the overall thermal conductivity efficiency is limited. Although the chemical modification method has improved the dispersion and interface bonding strength of the filler to a certain extent and improved the thermal conductivity, the high cost and complex process flow limit its widespread application.
[0004] In addition, thermal conductive silicone cloth must also have good friction properties in practical applications to cope with complex and changeable working environments and mechanical stresses. However, thermal conductive silicone cloth prepared by existing technologies often performs poorly in friction properties and is prone to problems such as wear and slippage, which not only affects the service life of the product, but also limits its application potential in high-precision and high-requirement fields.
[0005] Therefore, the present invention provides a friction-resistant thermally conductive silicone cloth and a preparation method thereof. Summary of the invention
[0006] The object of the present invention is to provide a friction-resistant thermally conductive silicone cloth and a preparation method thereof, so as to obtain the friction-resistant thermally conductive silicone cloth having the characteristics of high thermal conductivity, low thermal resistance, low friction coefficient and the like.
[0007] The purpose of the present invention is achieved by the following technical solutions:
[0008] In one aspect, the present invention provides a friction-resistant thermally conductive silicone cloth comprising the following parts by weight:
[0009] 50-100 parts of porous flake boron nitride;
[0010] 1-2 portions of saturated fatty acids;
[0011] 30-40 parts of vinyl silicone oil;
[0012] 5-10 parts of hydrogen silicone oil;
[0013] Catalyst 0.01-0.02 parts;
[0014] Inhibitor 0.01-0.02 parts.
[0015] Furthermore, the mass ratio of the porous boron nitride to the saturated fatty acid is 100:1;
[0016] Furthermore, the mass ratio of the vinyl silicone oil to the hydrogen-containing silicone oil is 5:1;
[0017] Furthermore, the mass ratio of the thermally conductive powder to the silicone oil matrix is (1-3):1, wherein the silicone oil matrix comprises vinyl silicone oil and hydrogenated silicone oil in a mass ratio of 1;
[0018] Further, the mass of the inhibitor accounts for 0.02wt% of the total system;
[0019] Furthermore, the mass of the catalyst accounts for 0.02 wt% of the total system.
[0020] Furthermore, the porous flake boron nitride has a particle size of 1-30 μm and a thickness of 10-50 nm;
[0021] Furthermore, the average diameter of the holes on the porous boron nitride sheet is 200 nm;
[0022] Furthermore, the saturated fatty acid is one or more combinations of stearic acid, oleic acid, and lauric acid;
[0023] Furthermore, the viscosity of the vinyl silicone oil is 500-1000 mPa·s;
[0024] Furthermore, the viscosity of the hydrogen-containing silicone oil is 10-500 mPa·s;
[0025] Furthermore, the catalyst is a platinum catalyst, and the platinum content in the platinum catalyst is 5000ppm;
[0026] Furthermore, the inhibitor is an alkynol inhibitor.
[0027] Furthermore, the porous boron nitride flakes have a particle size of 20 μm and a thickness of 20 nm;
[0028] Furthermore, the saturated fatty acid includes stearic acid and lauric acid, and the mass ratio of stearic acid to lauric acid is 2:1;
[0029] Furthermore, the viscosity of the vinyl silicone oil is 500 mPa·s;
[0030] Furthermore, the viscosity of the hydrogen-containing silicone oil is 50 mPa·s.
[0031] On the other hand, the present invention provides a method for preparing a friction-resistant thermally conductive silicone cloth, wherein the friction-resistant thermally conductive silicone cloth is the friction-resistant thermally conductive silicone cloth described above;
[0032] The preparation method comprises:
[0033] Step a: hydroxylating the surface of the porous flake boron nitride to obtain a modified porous flake boron nitride;
[0034] Step b: by chemical adsorption, the carboxyl group of the saturated fatty acid reacts with the hydroxyl group on the surface of the modified porous boron nitride sheet to form a chemical bond graft to obtain a thermal conductive filler;
[0035] Step c: uniformly mixing the thermal conductive filler, vinyl silicone oil, hydrogen-containing silicone oil and inhibitor to obtain a first mixture;
[0036] Step d: adding a catalyst to the first mixture and mixing them uniformly to obtain a second mixture;
[0037] Step e: coating the second mixture on the surface of the glass fiber cloth, drying and forming the mixture, and obtaining a friction-resistant thermally conductive silicone cloth.
[0038] Further, the step a comprises:
[0039] The porous boron nitride flakes are placed in a muffle furnace at 1000-1300°C, and oxygen is introduced into the muffle furnace to sinter the porous boron nitride flakes;
[0040] The porous flake boron nitride sintered for 1 hour or longer is placed in deionized water for quenching, and then centrifuged for drying to achieve surface hydroxylation of the porous flake boron nitride, thereby obtaining modified porous flake boron nitride.
[0041] Further, the step b comprises:
[0042] In a reaction system with a temperature of 100-150° C., the modified porous flake boron nitride is reacted with a saturated fatty acid for 1-2 hours to obtain a thermally conductive filler.
[0043] Further, the step e comprises:
[0044] The second mixture is coated on the surface of the glass fiber cloth, and the second mixture is evenly covered on the surface of the glass fiber cloth through a calendering process to obtain a coating layer with a thickness of 0.02-0.05 mm, and then vulcanized and formed through a drying oven to form a friction-resistant thermally conductive silicone cloth.
[0045] Furthermore, in the step e:
[0046] The calendering pressure is 5MPa; the drying temperature is 100-150°C, and the drying time is 30min.
[0047] Furthermore, the mass ratio of the porous boron nitride to the saturated fatty acid is 100:1;
[0048] Furthermore, the mass ratio of the vinyl silicone oil to the hydrogen-containing silicone oil is 5:1;
[0049] Furthermore, the mass ratio of the thermally conductive powder to the silicone oil matrix is (1-3):1, wherein the silicone oil matrix comprises vinyl silicone oil and hydrogenated silicone oil in a mass ratio of 1;
[0050] Further, the mass of the inhibitor accounts for 0.02wt% of the total system;
[0051] Further, the mass of the catalyst accounts for 0.02wt% of the total system;
[0052] Furthermore, the porous flake boron nitride has a particle size of 1-30 μm and a thickness of 10-50 nm;
[0053] Furthermore, the average diameter of the holes on the porous boron nitride sheet is 200 nm;
[0054] Furthermore, the saturated fatty acid is one or more combinations of stearic acid, oleic acid, and lauric acid;
[0055] Furthermore, the viscosity of the vinyl silicone oil is 500-1000 mPa·s;
[0056] Furthermore, the viscosity of the hydrogen-containing silicone oil is 10-500 mPa·s;
[0057] Furthermore, the catalyst is a platinum catalyst, and the platinum content in the platinum catalyst is 5000ppm;
[0058] Furthermore, the inhibitor is an alkynol inhibitor.
[0059] Compared with the prior art, the beneficial effects of the present invention include at least:
[0060] The present invention uses porous flaky boron nitride with extremely low intrinsic friction coefficient as the basic material. Its unique lamellar structure can effectively slide when subjected to friction, naturally reducing friction resistance. Furthermore, by modifying the porous flaky boron nitride, the carboxyl group of the saturated fatty acid reacts chemically with the hydroxyl group on the surface of the boron nitride to achieve chemical bond grafting, which not only gives the thermal conductive filler the ability to store heat through phase change, but also causes the saturated fatty acid layer on the surface of the modified porous flaky boron nitride to undergo a solid-liquid phase change when the friction-resistant thermal conductive silicone cloth encounters friction. This phase change process not only effectively absorbs and dissipates a large amount of heat energy generated by friction, but also the saturated fatty acid layer after the phase change also has an excellent lubricating effect. Under the combined effect, the friction coefficient of the friction-resistant thermal conductive silicone cloth is greatly reduced, its friction resistance is significantly improved, and its application prospects are broadened.
[0061] The present invention adopts a saturated fatty acid chemical bond grafting method to modify the porous flake boron nitride to prepare a thermal conductive filler, and vinyl silicone oil and hydrogen-containing silicone oil are mixed in a certain proportion, coated and calendered on the surface of the glass fiber cloth, and cured and formed by chemical addition reaction to obtain a wear-resistant thermal conductive silicone cloth with high thermal conductivity, low thermal resistance, low friction coefficient, etc. The thermal conductivity of the wear-resistant thermal conductive silicone cloth of the present invention can reach 5.835W / m·K, the thermal resistance can reach 0.301℃*in2 / W, and the friction coefficient can reach 0.12. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 The present invention is a schematic diagram of a method for preparing a friction-resistant thermally conductive silicone cloth according to an embodiment of the present invention. DETAILED DESCRIPTION
[0063] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided to make the present invention more comprehensive and complete and to fully convey the concepts of example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their repeated description will be omitted.
[0064] The words expressing positions and directions described in the present invention are all explained with reference to the accompanying drawings as examples, but they can be changed as needed, and all such changes are included in the protection scope of the present invention.
[0065] Traditional thermal conductive filler preparation technology often faces the challenge of insufficient thermal conductivity. Even if the advanced chemical bond grafting method is used, the thermal conductive filler obtained is still unable to cope with the increasing application requirements. To address this problem, the present invention modifies the porous flake boron nitride, so that the carboxyl group of the saturated fatty acid reacts chemically with the hydroxyl group on the surface of the boron nitride to obtain a thermal conductive filler, and optimizes its filling ratio, thereby improving the thermal conductivity of the wear-resistant thermal conductive silicone cloth.
[0066] In addition, the existing friction-resistant thermal conductive silicone cloth generally has poor friction performance, which not only weakens its mechanical durability, but also greatly limits the expansion of its application field. To solve this problem, the present invention selects porous flake boron nitride with extremely low intrinsic friction coefficient as the basic material. Its unique lamellar structure can effectively slide when subjected to friction, naturally reducing friction resistance. Furthermore, by modifying the porous flake boron nitride, the carboxyl group of the saturated fatty acid reacts chemically with the hydroxyl group on the surface of the boron nitride to achieve chemical bond grafting, which not only gives the thermal conductive filler the ability to store heat through phase change, but also causes the saturated fatty acid layer on the surface of the modified porous flake boron nitride to undergo solid-liquid phase change when the friction-resistant thermal conductive silicone cloth encounters friction. This phase change process not only effectively absorbs and dissipates a large amount of heat energy generated by friction, but also the saturated fatty acid layer after the phase change also has an excellent lubricating effect. Under the combined effect, the friction coefficient of the friction-resistant thermal conductive silicone cloth is greatly reduced, its friction resistance is significantly improved, and the application prospects are broadened.
[0067] Next, the wear-resistant thermally conductive silicone cloth and the preparation method thereof of the present invention are introduced.
[0068] The friction-resistant heat-conductive silicone cloth of the present invention comprises the following components by weight: 50-100 parts of porous flake boron nitride; 1-2 parts of saturated fatty acid; 30-40 parts of vinyl silicone oil; 5-10 parts of hydrogen-containing silicone oil; 0.01-0.02 parts of catalyst; and 0.01-0.02 parts of inhibitor.
[0069] In some preferred embodiments, the mass ratio of porous flake boron nitride to saturated fatty acid is 100:1; the mass ratio of vinyl silicone oil to hydrogen-containing silicone oil is 5:1; the mass ratio of thermal conductive powder to silicone oil matrix is (1-3):1, wherein the silicone oil matrix comprises vinyl silicone oil and hydrogen-containing silicone oil in a mass ratio of 1; the mass of the inhibitor accounts for 0.02wt% of the total system; the mass of the catalyst accounts for 0.02wt% of the total system.
[0070] The porous boron nitride has a particle size of 1-30 μm (for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 20 μm, 30 μm), and a thickness of 10-50 nm (for example, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 30 nm, 40 nm, 50 nm); the average diameter of the holes on the porous boron nitride is 200 nm.
[0071] In some preferred embodiments, the particle size of the porous boron nitride flakes is 20 μm and the thickness is 20 nm. The porous boron nitride flakes are purchased from Saint-Gobain, France, and the model is boron nitride CFP series.
[0072] The saturated fatty acid of the present invention is one or more combinations of stearic acid, soft acid and lauric acid. Among them, stearic acid is purchased from Malaysian Coconut Tree brand, model is industrial grade 1801; soft acid is purchased from Malaysian Coconut Tree brand, model is industrial grade 1699; lauric acid is purchased from Malaysian Coconut Tree brand, model is C1299.
[0073] In some preferred embodiments, the mass fraction of saturated fatty acid is 1% of the mass fraction of porous flake boron nitride. Further, the saturated fatty acid includes stearic acid and lauric acid, and the mass fraction ratio of stearic acid to lauric acid is 2:1.
[0074] The viscosity of the vinyl silicone oil of the present invention is 500-1000mPa·s (for example: 500mPa·s, 550mPa·s, 600mPa·s, 650mPa·s, 700mPa·s, 750mPa·s, 800mPa·s, 850mPa·s, 900mPa·s, 950mPa·s, 1000mPa·s); the viscosity of the hydrogen-containing silicone oil is 10-500mPa·s (for example: 10mPa·s, 50mPa·s, 100mPa·s, 150mPa·s, 200mPa·s, 250mPa·s, 300mPa·s, 350mPa·s, 400mPa·s, 450mPa·s, 500mPa·s), and the mass ratio of the vinyl silicone oil to the hydrogen-containing silicone oil is 1. The content of hydrogen atoms in the hydrogen-containing silicone oil is 0.4 wt %.
[0075] In some preferred embodiments, the mass ratio of vinyl silicone oil to hydrogen-containing silicone oil is 5:1. Further, the viscosity of the vinyl silicone oil is 500mPa·s; the viscosity of the hydrogen-containing silicone oil is 50mPa·s. Vinyl silicone oil was purchased from Jiangxi Haiduo Silicone Co., Ltd., with a viscosity of 500mPa·s as model HV500 and a viscosity of 1000mPa·s as model HV1000. Vinyl silicone oil was also purchased from Anbiya Special Silicone Co., Ltd., with a viscosity of 500mPa·s as model 500CV and a viscosity of 1000mPa·s as model 1000CV.
[0076] The hydrogen-containing silicone oil includes two types: end-hydrogen-containing and side-hydrogen-containing. They were purchased from Anbia Special Silicone Co., Ltd. The model of the side-hydrogen-containing hydrogen-containing silicone oil with a viscosity of 50mPa·s is XL17, the model of the side-hydrogen-containing hydrogen-containing silicone oil with a viscosity of 100mPa·s is XL13, the model of the side-hydrogen-containing hydrogen-containing silicone oil with a viscosity of 500mPa·s is XL12, the model of the end-hydrogen-containing hydrogen-containing silicone oil with a viscosity of 30mPa·s is CE30LV, the model of the end-hydrogen-containing hydrogen-containing silicone oil with a viscosity of 100mPa·s is CE100, and the model of the end-hydrogen-containing hydrogen-containing silicone oil with a viscosity of 500mPa·s is CE500.
[0077] The catalyst of the present invention is a platinum catalyst, and the platinum content in the platinum catalyst is 5000ppm. The platinum catalyst is purchased from Anbiya Special Silicone Co., Ltd., and the model is 50175F.
[0078] The inhibitor of the present invention is an alkynol inhibitor, which is purchased from Anbiya Special Silicone Co., Ltd. and has a model number of TMDO.
[0079] refer to Figure 1 The method for preparing the above-mentioned wear-resistant thermally conductive silicone cloth of the present invention comprises: steps a to e.
[0080] Step a: hydroxylating the surface of porous flake boron nitride to obtain modified porous flake boron nitride.
[0081] When used, the porous flake boron nitride is placed in a muffle furnace at 1000-1300° C., and oxygen is introduced into the muffle furnace to sinter the porous flake boron nitride; the porous flake boron nitride after sintering for a time greater than or equal to 1 hour is placed in deionized water for quenching treatment, and then centrifugally dried to achieve surface hydroxylation of the porous flake boron nitride, thereby obtaining modified porous flake boron nitride.
[0082] In practical applications, the surface of hydroxylated porous boron nitride sheet includes the following formula:
[0083] 4BN+7O2=2B2O 3+ 4NO2
[0084] 2B2O3+6H2O=4H3BO3.
[0085] Step b: by chemical adsorption, the carboxyl group of the saturated fatty acid reacts with the hydroxyl group on the surface of the modified porous flake boron nitride to form a chemical bond graft to obtain a thermal conductive filler.
[0086] When used, the modified porous flaky boron nitride is reacted with saturated fatty acids for 1-2 hours (e.g., 1 hour, 1.1 hour, 1.2 hour, 1.3 hour, 1.4 hour, 1.5 hour, 1.6 hour, 1.7 hour, 1.8 hour, 1.9 hour, 2 hour) in a reaction system at a temperature of 100-150°C (e.g., 100°C, 110°C, 120°C, 130°C, 140°C, 150°C) to obtain a thermally conductive filler. Specifically, the porous lamellar structure of the porous flaky boron nitride can increase the specific surface area of the reaction, so that more saturated fatty acids are adsorbed inside the pores, thereby obtaining a thermally conductive filler with good thermal conductivity and friction properties.
[0087] In practical applications, the reaction between the carboxyl group of the saturated fatty acid and the hydroxyl group on the surface of the modified porous boron nitride sheet includes the following formula:
[0088] H3BO3+3CH3(CH2) n COOH=B(CH3(CH2) n COO)3+3H2O
[0089] In the formula, the value range of n is 8-20, and the preferred values are 10, 14, and 16.
[0090] Step c: uniformly mixing the thermal conductive filler, vinyl silicone oil, hydrogen-containing silicone oil and inhibitor to obtain a first mixture.
[0091] When used, the weight proportions of the raw materials are: 50-100 parts of porous flake boron nitride; 1-2 parts of saturated fatty acid; 30-40 parts of vinyl silicone oil; 5-10 parts of hydrogen-containing silicone oil; and 0.01-0.02 parts of inhibitor.
[0092] Step d: adding a catalyst to the first mixture and mixing them uniformly to obtain a second mixture.
[0093] When used, the mass fraction of the catalyst is 0.01-0.02 parts, and the viscosity of the second mixture is 500-1000 mPa·s.
[0094] Step e: coating the second mixture on the surface of the glass fiber cloth, drying and forming the mixture, and obtaining a friction-resistant thermally conductive silicone cloth.
[0095] When used, the second mixture is coated on the surface of the glass fiber cloth, and the second mixture is evenly covered on the surface of the glass fiber cloth through a calendering process to obtain a coating layer with a thickness of 0.02-0.05mm (for example: 0.02mm, 0.03mm, 0.04mm, 0.05mm), and then vulcanized and formed through a drying oven to form a wear-resistant thermally conductive silicone cloth.
[0096] The calendering pressure is 5 MPa; the temperature of the drying oven is 100-150°C (for example: 100°C, 110°C, 120°C, 130°C, 140°C, 150°C), and the drying oven time is 30 minutes.
[0097] In practical application, the process steps of drying tunnel vulcanization molding include the following:
[0098] R-SiH3+R`-Si(CH=CH2)3→R-Si(R`-Si(CH=CH2)2H)3
[0099] Wherein, R and R' are abbreviations for the long chain ends of vinyl silicone oil and hydrogen silicone oil.
[0100] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0101] Example 1-5 A friction-resistant thermally conductive silicone cloth is prepared according to the above preparation method. Specifically, the process parameters of Example 1-5 are detailed in Table 1. The performance parameters of the product (friction-resistant thermally conductive silicone cloth) obtained in Example 1-5 are detailed in Table 2. The standards for measuring various parameters are detailed in Table 3.
[0102] Table 1 Process parameters of Examples 1-5
[0103]
[0104]
[0105] Table 2 Performance parameters of the products obtained in Examples 1-5 (friction-resistant thermally conductive silicone cloth)
[0106]
[0107]
[0108] Table 3 Standards for determination of various parameters
[0109]
[0110] In summary, the present invention uses saturated fatty acid chemical bond grafting to modify porous boron nitride to improve the thermal conductivity and friction performance of the thermal conductive filler. In addition, the thermal conductive filler is mixed with vinyl silicone oil and hydrogen-containing silicone oil in a certain proportion, coated and calendered on the surface of the glass fiber cloth, and then cured and formed by chemical addition reaction to obtain a friction-resistant thermal conductive silicone cloth.
[0111] Specifically, the present invention adjusts the type of saturated fatty acid and its mass ratio to porous flake boron nitride, adjusts the mixing ratio of thermally conductive filler and silicone oil matrix, and further controls the addition reaction conditions of drying tunnel vulcanization molding to improve the friction performance and thermal conductivity of the wear-resistant thermally conductive silicone cloth.
[0112] The friction-resistant heat-conductive silicone cloth of the present invention can be widely used due to its good thermal conductivity, thermal resistance, friction performance, and dielectric properties, for example, in the fields of polymer materials, thermal management materials, and tribology.
[0113] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, substitute and modify the above embodiments within the scope of the invention without departing from the principles and purpose of the present invention. All such changes should fall within the scope of protection of the claims of the present invention.
Claims
1. A friction-resistant heat-conductive silicone cloth, characterized in that: It comprises the following mass fractions: 50-100 parts of porous flake boron nitride; 1-2 portions of saturated fatty acids; 30-40 parts of vinyl silicone oil; 5-10 parts of hydrogen silicone oil; Catalyst 0.01-0.02 parts; Inhibitor 0.01-0.02 parts.
2. The friction-resistant heat-conductive silicone cloth according to claim 1, characterized in that: The mass ratio of the porous boron nitride to the saturated fatty acid is 100:1; The mass ratio of the vinyl silicone oil to the hydrogen-containing silicone oil is 5:1; The mass ratio of the thermally conductive powder to the silicone oil matrix is (1-3):1, wherein the silicone oil matrix comprises vinyl silicone oil and hydrogen-containing silicone oil in a mass ratio of 1; The mass of the inhibitor accounts for 0.02wt% of the total system; The mass of the catalyst accounts for 0.02 wt% of the total system.
3. The friction-resistant heat-conductive silicone cloth according to claim 1, characterized in that: The porous boron nitride flakes have a particle size of 1-30 μm and a thickness of 10-50 nm; and / or, The average diameter of the holes in the porous boron nitride sheet is 200 nm; and / or, The saturated fatty acid is one or more combinations of stearic acid, oleic acid and lauric acid; and / or, The viscosity of the vinyl silicone oil is 500-1000 mPa·s; and / or, The viscosity of the hydrogen-containing silicone oil is 10-500 mPa·s; and / or, The catalyst is a platinum catalyst, and the platinum content in the platinum catalyst is 5000ppm; and / or, The inhibitor is an alkynol inhibitor.
4. The friction-resistant heat-conductive silicone cloth according to claim 1, characterized in that: The porous boron nitride flakes have a particle size of 20 μm and a thickness of 20 nm; and / or, The saturated fatty acid comprises stearic acid and lauric acid, and the mass ratio of stearic acid to lauric acid is 2:1; and / or, The viscosity of the vinyl silicone oil is 500 mPa·s; and / or, The viscosity of the hydrogen-containing silicone oil is 50 mPa·s.
5. A method for preparing friction-resistant heat-conductive silicone cloth, characterized in that: The friction-resistant heat-conductive silicone cloth is the friction-resistant heat-conductive silicone cloth according to any one of claims 1 to 4; The preparation method comprises: Step a: hydroxylating the surface of the porous flake boron nitride to obtain a modified porous flake boron nitride; Step b: by chemical adsorption, the carboxyl group of the saturated fatty acid reacts with the hydroxyl group on the surface of the modified porous boron nitride sheet to form a chemical bond graft to obtain a thermal conductive filler; Step c: uniformly mixing the thermal conductive filler, vinyl silicone oil, hydrogen-containing silicone oil and inhibitor to obtain a first mixture; Step d: adding a catalyst to the first mixture and mixing them uniformly to obtain a second mixture; Step e: coating the second mixture on the surface of the glass fiber cloth, drying and forming the mixture, and obtaining a friction-resistant thermally conductive silicone cloth.
6. The method for preparing the friction-resistant heat-conductive silicone cloth according to claim 5, characterized in that: The step a comprises: The porous boron nitride flakes are placed in a muffle furnace at 1000-1300°C, and oxygen is introduced into the muffle furnace to sinter the porous boron nitride flakes; The porous flake boron nitride sintered for 1 hour or longer is placed in deionized water for quenching, and then centrifuged for drying to achieve surface hydroxylation of the porous flake boron nitride, thereby obtaining modified porous flake boron nitride.
7. The method for preparing the friction-resistant heat-conductive silicone cloth according to claim 5, characterized in that: The step b comprises: In a reaction system with a temperature of 100-150° C., the modified porous flake boron nitride is reacted with a saturated fatty acid for 1-2 hours to obtain a thermally conductive filler.
8. The method for preparing the friction-resistant heat-conductive silicone cloth according to claim 5, characterized in that: The step e comprises: The second mixture is coated on the surface of the glass fiber cloth, and the second mixture is evenly covered on the surface of the glass fiber cloth through a calendering process to obtain a coating layer with a thickness of 0.02-0.05 mm, and then vulcanized and formed through a drying oven to form a friction-resistant thermally conductive silicone cloth.
9. The method for preparing the friction-resistant heat-conductive silicone cloth according to claim 8, characterized in that: In the step e: The calendering pressure is 5MPa; the drying temperature is 100-150°C, and the drying time is 30min.
10. The method for preparing the friction-resistant heat-conductive silicone cloth according to claim 5, characterized in that: The mass ratio of the porous boron nitride to the saturated fatty acid is 100:1; and / or, The mass ratio of the vinyl silicone oil to the hydrogen-containing silicone oil is 5:1; and / or, The mass ratio of the thermally conductive powder to the silicone oil matrix is (1-3):1, wherein the silicone oil matrix comprises vinyl silicone oil and hydrogen silicone oil in a mass ratio of 1; and / or, The mass of the inhibitor accounts for 0.02wt% of the total system; and / or, The mass of the catalyst accounts for 0.02wt% of the total system; and / or, The porous boron nitride flakes have a particle size of 1-30 μm and a thickness of 10-50 nm; and / or, The average diameter of the holes in the porous boron nitride sheet is 200 nm; and / or, The saturated fatty acid is one or more combinations of stearic acid, oleic acid and lauric acid; and / or, The viscosity of the vinyl silicone oil is 500-1000 mPa·s; and / or, The viscosity of the hydrogen-containing silicone oil is 10-500 mPa·s; and / or, The catalyst is a platinum catalyst, and the platinum content in the platinum catalyst is 5000ppm; and / or, The inhibitor is an alkynol inhibitor.